Incidence and risk factors of pulmonary complications after lumbar spine surgery, 2010–2019 - Liping Huang; Linglu Hu; Yiting Huang; Qinfeng Yang; Jian Wang; Huirong Chen; Xiaodan Li (Perioperative Medicine)
Abstract Background The occurrence of pulmonary complications is common following major surgery, resulting in a diversity of detrimental outcomes. Nevertheless, there is a dearth of documentation examining the occurrence rate of pulmonary complications and related hazard factors following lumbar spine surgery by using a large-scale national database. Methods We conducted a retrospective database analysis from 2010 to 2019 by using the Nationwide Inpatient Sample (NIS). Patients undergoing lumbar spine surgery were included in the study. Patient demographics, in-hospital mortality, insurance type, total charges, hospital type, length of stay in hospital (LOS), preoperative comorbidities, as well as medical and surgical complications were appraised. Results In total, 932,563 lumbar spine operations were recorded in the NIS database from 2010 to 2019. The overall incidence of pulmonary complications following lumbar spine surgery was 3.54%. Patients with pulmonary complications after lumbar spine surgery presented prolonged LOS, higher in-hospital charges, and more preoperative complications (p < 0.001). Many preoperative comorbidities and postoperative complications were associated with pulmonary complications, which involved alcohol abuse, deficiency anemia, coagulopathy, diabetes (uncomplicated), drug abuse, metastatic cancer, psychoses, renal failure, weight loss, blood transfusion, cardiac arrest, postoperative delirium, septicemia, thrombocytopenia, hemorrhage/seroma/hematoma, nerve injuries and wound infection. Additionally, advanced age (≥ 75 years), number of comorbidity, type of insurance (Medicaid and Private insurance), teaching hospital, urban hospital were also associated with pulmonary complications. Conclusions The results of our study revealed a relatively low incidence of pulmonary complications subsequent to lumbar spine surgery. Investigating risk factors associated with postoperative pulmonary complications can be beneficial in ensuring proper management and mitigating the adverse effects.